PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA PADA GURU SD DI KECAMATAN SLUKE KABUPATEN REMBANG - Suradi, 12.52.02.0179; Sutomo, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to examine and analyze that job satisfaction memodiasi motivation and discipline to the performance of the primary school teachers in the district Sluke Rembang. Sampling was done by census method so that all teachers working in elementary schools in District of Rembang Sluke numbering 124 man. Mechanical testing of the data used in this study include testing the validity of the factor analysis, reliability testing with Cronbach alpha formula, multiple regression analysis, and the significance test, the coefficient of determination to prove the truth of the research hypothesis and testmediation. The results showed that; motivation has no effect on job satisfaction, work discipline and a significant positive effect on job satisfaction, motivation positive and significant impact on the performance of teachers, labor discipline does not affect the performance of teachers, job satisfaction does not affect the performance of teachers, motivation mediation does not affect the job satisfaction teacher performance, discipline mediation work with job satisfaction affect the performance of teachers in publik primary schools in District Sluke Rembang. Keywords : motivation, work discipline, job satisfaction, performance.